Three-Dimensional Printed Facial Models in Rhinoplasty - Klosterman, Tristan; Romo III, Thomas (Facial Plastic Surgery, 2018)
Digital patient photography and morphing software have become an important part of rhinoplasty over the past few decades. Presented is a novel technology incorporating 3D photography and printing to produce life-size models for use in patient evaluation and treatment. Surveys were conducted to assess patient response and were universally positive. Early surgeon experience also indicates benefit for intraoperative use. Three-dimensional printing and modeling is a new technology that has exciting applications for rhinoplasty and facial plastic surgery.
Keywords: rhinoplasty; 3D printing; technology; facial plastics